Lifestyle and cardiovascular risk in asymptomatic individuals in the Kenitra region, Morocco - El Ghouddany, Safouane; Lahmam, Mohamed; Hmimou, Rachid; Boumaghzel, Sanae; Yamni, Khalid; Zeghari, Lotfi; Lachhab, Btissam; Fnesh, Driss; Ouhssine, Mohammed (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Cardiovascular illnesses are the foremost cause of death globally, accounting for around 17.9 million fatalities per year. In Morocco, the national death rate attributable to cardiovascular diseases has attained 38%. The objective of our study is to identify asymptomatic individuals at risk of developing cardiovascular disease and to find the link between this risk and several factors in the province of Kenitra, a city in northeastern Morocco.Methods: This cross-sectional study was performed at the Zemouri provincial hospital, over a period of more than three months. The assessment of socio-demographic factors and lifestyle was based on a questionnaire. About Anthropometry, an electronic scale was used to obtain weight (in kg) with an accuracy of 0.1 kg, and a measuring rod with an accuracy of 0.1 cm was used to measure height (in m). Obesity was assessed based on BMI (kg/m²). The blood pressure was measured using arm blood pressure monitors, blood sugar was measured using a glucometer, and total cholesterol, triglycerides, LDL and HDL cholesterol were measured using a lipid profile analyzer. Regarding cardiovascular risk, an estimation was made using the "office-based" table of the Globorisk score in Morocco.Results: According to our results the majority of people (40.91%) have a high cardiovascular risk, 34.85% have a moderate risk, and 24.24% have a low risk. Also, a strong and statistically significant positive correlation between age and cardiovascular risk (r=0.74; p=0.00) and between systolic blood pressure and cardiovascular risk (r=0.69; P=0.00), as well as a notable prevalence of obesity (48.48%) and 25.68% have high blood pressure.Conclusions: Our study revealed the presence of cardiovascular risk in certain asymptomatic individuals, even though it affects only a small number of people. This calls for constant vigilance, and the general public must be warned of the increasing seriousness of the situation.